A critical examination of government budgeting and public funds management in Nigeria. Issue 4 (20th November 2017) - Ajibolade, Solabomi Omobola; Oboh, Collins Sankay
Abstract : Purpose: The purpose of this paper is to attempt an empirical examination of government budgeting and expenditure processes in Nigeria, a developing country. It examines the current state of budgeting and public funds management (PFM) in Nigeria. It also examines the extent to which the government has used the budgetary mechanism to effectively manage the nation's economy. Design/methodology/approach: The paper employed simple regression estimation technique for data analysis. Time series data set of budgetary information was constructed from different archival sources over a 16-years period (2000-2015), majorly the national Appropriation Acts, press releases, regulatory and governmental reports, reports of Transparency International, World Bank and Central Intelligence Agency. Findings: The findings confirm that the nation's annual budgeting approach is defective and lags in achieving its fiscal objectives. The budget indicates a state of poor accountability and transparency in PFM. Findings also suggest that the level of economic development in Nigeria is not commensurate with the size of government expenditure. Practical implications: The paper draws the attention of the government to the need to restructure its approach to budgeting and adopt a more resilient approach that suits its environment and economic peculiarities in effort to ensure efficient management and accountability of public funds. The paper also offers value to other developing countries. It provides empirical evidence that explains an aspect why the African continent remains underdeveloped hitherto. Originality/value: This paper lends a voice to the call for a restructuring of the Nigerian budgetary system and its implementation strategy. It advocates for the adoption of an alternative budgeting approach that matches Nigeria economic realities. The paper demonstrated that the traditional budgetary approach being used by many developing countries is limited in certain ways and could hinder sustainable development.